Global and local perspectives on B2B branding - Ambroselli, Holger (Henry Stewart Talks, 2008)
Brands and markets, A new brand building process, 'Push' and 'pull' branding, Future attraction of markets, Cultural differences, The Asian challenge, Cultural understanding, Cultural differences as a challenge, Power distance, Status needs |Individualism versus collectivism, Convergence and divergence in consumer behaviour, Uncertainty avoidance, Advertising and communication styles that respect cultural differences, Buying motives
Archived at 2022/03/17